Expression of Human ACE2 N-terminal Domain, Part of the Receptor for SARS-CoV-2, in Fusion With Maltose-Binding Protein, E. coli Ribonuclease I and Human RNase A - Xu, Shuang-yong; Fomenkov, Alexey; Chen, Tien-Hao; Yigit, Erbay (Frontiers in Microbiology, 2021)
The SARS-CoV-2 viral genome contains a positive-strand single-stranded RNA of ~30 kb. Human ACE2 protein is the receptor for SARS-CoV-2 virus attachment and infection. We propose to use ribonucleases (RNases) as antiviral agents to destroy the viral genome in vitro. In the virions the RNA is protected by viral capsid proteins, membrane proteins and nucleocapsid proteins. To utilize RNases as antiviral strategy we set out to construct RNase fusion with human ACE2 receptor N-terminal domain (ACE2NTD). We expressed six proteins in E. coli cells: 1) MBP-ACE2NTD, 2) ACE2NTD-GFP, 3) RNase I (6xHis), 4) RNase III (6xHis), 5) RNase I-ACE2NTD (6xHis), and 6) human RNase A-ACE2NTD (6xHis). We evaluated fusion expression in different E. coli strains, partially purified MBP-ACE2NTD protein from the soluble fraction of bacterial cell lysate, and refolded MBP-ACE2NTD protein from inclusion body. The engineered RNase I-ACE2NTD (6xHis) and hRNase A-ACE2NTD (6xHis) fusions are active in cleaving SARS-CoV-2 RNA fragment in vitro. The recombinant RNase I (6xHis) and RNase III (6xHis) are active in cleaving RNA and dsRNA in test tube. This study provides a proof-of-concept for construction of fusion protein between human receptor and nuclease that may be used to degrade viral nucleic acids.